METHODS OF INCREASING THE EFFICIENCY OF TECHNOLOGICAL MACHINES IN INDUSTRIAL ENTERPRISES (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This scientific article provides an in-depth analysis of the issues of increasing the efficiency of technological machines in industrial enterprises. It covers the impact of monitoring the technical condition of technological machines, automated control systems, energy-saving technologies, planned maintenance, modernization and digitalization processes on production efficiency. Each approach is scientifically explained and indicated as factors that contribute to the continuity of production processes, economic efficiency and product quality. The role of the human factor, operator skills and the level of technical culture are also assessed as important factors affecting efficiency. This study contains practical recommendations for more efficient operation of technological machines and is relevant in a modern industrial production environment.